Efficiency Analysis of Wireless Power Transfer System Based on PCB Magnetic Resonance Coil - LI Zhiyong; ZHOU Fangyi; LI Xiaoguang; CHEN Yougen (Kongzhi Yu Xinxi Jishu)
Magnetic resonance wireless power transmission technology has become a research focuse due to its characteristic of far distance and high efficiency. Four-coil magnetic resonant wireless power transmission system model was presented and the system transmission efficiency was analyzed by mutual inductance coupling circuit models. Putting forward a step by step analysis method, it clearly showed the relationship of energy transfer efficiency between coils. Resistance, detuning factor and coupling coefficient factor have been derived as important factors affecting transmission efficiency. On the basis of several application scenarios, a new type of PCB magnetic resonance coil system was designed. The above analysis was verified, which could provide a basis for the later optimization design.